Ventricular Arrhythmias in Patients with Obstructive Sleep Apnea - Marinheiro, Rita (Curr Cardiol Rev, 2019)
Obstructive Sleep Apnea (OSA) is a prevalent condition thought to increase in the future. Being mostly undiagnosed, the most serious complications are cardiovascular diseases, among which are arrhythmias. Controversy remains as to whether OSA is a primary etiologic factor for ventricular arrhythmias, because of the high incidence of cardiovascular comorbidities in OSA patients. Howev-er, there is mostly a strong evidence of a relation between OSA and ventricular arrhythmias. A few mechanisms have been proposed to be responsible for this association and some electrocardiographic changes have also been demonstrated to be more frequent in OSA patients. Treatment of OSA with Continuous Positive Airway Pressure (CPAP) has the potential to reduce arrhythmias and confer a mortality benefit.